RELATIONSHIP BETWEEN NEGATIVE CAREER THOUGHTS AND SELF-EFFICACY WITH CAREER DECISION-MAKING DIFFICULTIES AMONG FIRST YEAR UNDERGRADUATE STUDENTS OF UPM - Nur Azreen Md Sanusi; Zanariah Ismail, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
The purpose of this study is to determine the relationship between negative career thoughts and self-efficacy with career decision-making difficulties among first-year undergraduate students of UPM. The sample for this study consisted of 368 first-year undergraduate students of UPM and participants were recruited using stratified random sampling. A self-administered questionnaire was used to collect information. Career Thoughts Inventory was utilized in this study to measure negative career thoughts. General Self-efficacy Scale was utilized to measure self-efficacy. Other than that, the Career Decision-Making Difficulties Questionnaire was utilized to measure career decision-making difficulties. The results revealed that most of the respondents had a high level of self-efficacy (62.2%). Pearson correlation analysis demonstrated that there was a positive significant relationship between negative career thoughts (decision-making confusion) and career decision-making difficulties (lack of information; r = 0.595, p < 0.01 and inconsistent information; r = 0.579, p < 0.01). Besides, there was also a significant positive relationship between negative career thoughts (commitment anxiety) and career decision-making difficulties (lack of information; r = 0.588, p < 0.01 and inconsistent information; r = 0.572, p < 0.01). In addition, there was a significant negative relationship between self-efficacy and career decision-making difficulties (lack of information; r = -0.388, p < 0.01, inconsistent information; r = -0.298, p < 0.01). Therefore, the findings of this study concluded that negative career thoughts and self-efficacy are important to understand the patterns of difficulties in career decision-making among first-year undergraduate students of UPM. Furthermore, further research could be expanded in different academic institutions in another region with a bigger sample to promote a better generalization of findings and yield more reliable data.